Pengaruh Penekanan Anggaran dan Kapasitas Individu terhadap Senjangan Anggaran pada Organisasi Perangkat Daerah Kabupaten Badung - Maheni, Ni Made Dwi; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 23 No 3 (2018), 2018)
A budget sla ck is a subordinate act that deliberately imposes a higher cost than it should and lower revenue than it should for the budget to be more easily achieved. There are several factors that can affect budget slack. This study aims to determine the effect of budgetary pressures and individual capacity on budgetary slack. This research was conducted at the Regional Device Organization of Badung Regency. The number of samples taken as many as 50 people, using nonprobability sampling method by purposive sampling. Data collection methods used were questionnaires, interviews and documentation. Analytical technique used multiple linear regression. Based on the results of the analysis it was found that budgetary pressures had a positive effect on budgetary slack and individual capacity negatively affecting budgetary slack. Keywords: budget, budget emphasis, individual capacity, budget slack